2015
DOI: 10.1021/nn507480v
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Sequential Substrate Binding at the Single-Molecule Level by Enzyme Mechanical Stabilization

Abstract: Enzyme-substrate binding is a dynamic process intimately coupled to protein structural changes, which in turn changes the unfolding energy landscape. By the use of single molecule force spectroscopy (SMFS), we characterize the open-to-closed conformational transition experienced by the hyperthermophilic ADP-dependent glucokinase from Thermococcus litoralis triggered by the sequential binding of substrates. In the absence of substrates, the mechanical unfolding of TlGK shows an intermediate I, which is stabiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…The preincubation of TlGK with AMP, AlCl 3 and NaF such that the concentration of AMP-AlF 3 formed is $1 mM, followed by titration with increasing concentrations of glucose, led to a notorious increase in fluorescence intensity (Fig. 3A), in good agreement with previous assessment of glucose binding in the presence of MgAMP [10]. We fitted the change in fluorescence intensity of wild type TlGK to Eq.…”
Section: Hxe Affects Binding Of Glucose For the Formation Of The Ternsupporting
confidence: 87%
See 2 more Smart Citations
“…The preincubation of TlGK with AMP, AlCl 3 and NaF such that the concentration of AMP-AlF 3 formed is $1 mM, followed by titration with increasing concentrations of glucose, led to a notorious increase in fluorescence intensity (Fig. 3A), in good agreement with previous assessment of glucose binding in the presence of MgAMP [10]. We fitted the change in fluorescence intensity of wild type TlGK to Eq.…”
Section: Hxe Affects Binding Of Glucose For the Formation Of The Ternsupporting
confidence: 87%
“…In line with this kinetic mechanism, small angle X-ray scattering and structure solution of TlGK in the presence of substrates and analogs have shown that the large and small domains of TlGK experience a sequential open-to-closed conformational transition, where MgADP À binding elicits a semi-closed state and the subsequent binding of glucose leads to formation of the ternary complex, triggering total domain closure [7]. Moreover, this sequential binding of substrates in TlGK has been recently confirmed by singlemolecule force spectroscopy experiments [10].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Specifically, we compare the unfolding mechanics of the modified pilus proteins with the intact Spy0128 and the mutant E258A, which lacks of isopeptide bond, as previously demonstrated (24). As shown in Figure 2B, our polyprotein constructs have two Spy0128 proteins flanked by titin I91 domains, used as fingerprint to discard spurious traces (24,35). When pulling intact Spy0128 constructs, only the three I91 domains unfold, which are identified as unfolding events with a contour length increment of 29 nm, as determined by fits to the worm-like chain model (36), and unfolding forces of ~200 pN (Figure 3A).…”
Section: Isopeptide-blocker Prevents the Folding Of Spy0128mentioning
confidence: 97%
“…We characterized the mechanical properties of the intact Spy0128 domain, and mutated Glu258Ala, where the isopeptide bond is abolished (15). In our polyprotein construct, two Spy0128 domains are flanked by I27 titin domains, allowing to use the I27 unfolding pattern as a fingerprint to discard spurious traces (14,17). While in the intact Spy0128 polyproteins only the I27 domains unfold (Figure 3A), the Glu258Ala mutant is extensible, showing a contour length increment of 50 nm, and an unfolding force of ~300 pN (Figure 3B).…”
Section: Isopeptide Blocker Prevents the Folding Of Spy0128mentioning
confidence: 99%